The Dead Sea scrolls at 60: scholarly contributions of New York University faculty and alumni - Schiffman, Lawrence H.; Tzoref, Shani (Studies on the texts of the desert of Judah 0169-9962, 2010)
The Judean desert scrolls and the history of Judaism and Christianity / Lawrence H. Schiffman -- The traditional roots of priestly messianism at Qumran / Joseph L. Angel -- The Dead Sea Scrolls and Jewish biblical interpretation in antiquity: a multi-generic perspective / Moshe J. Bernstein -- Zoroastrianism and Qumran / Yaakov Elman -- The Judean desert documents as a regional sub-tradition in Aramaic common law / Andrew D. Gross -- Law and exegesis in the Dead Sea Scrolls: the Sabbath carrying prohibition in comparative perspective / Alex P. Jassen -- On the identification of some two Greek fragments of 1 Enoch / Erik W. Larson -- The Copper Scroll (3Q15): a reconsideration / Judith K. Lefkovits -- Quotidian documents from the Judean desert / Baruch A. Levine -- Qumran Hebrew (with a trial cut [1QS]) / Gary A. Rendsburg -- Sectarians and householders / Alexei M. Sivertsev -- What is a scriptural text in the Second Temple period? : texts between their biblical past, their inner-biblical interpretation, their reception in Second Temple literature, and their textual witnesses / Mark S. Smith -- The "hidden" and the "revealed": esotericism, election, and culpability in Qumran and related literature / Shani Tzoref